The Effect of Micro, Small and Medium Enterprises on Economics Growth in Deli Serdang - Nova Alemina Br Manik; Irsad Lubis; Albar Tanjung (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstrakThis study seeks to examine the impact of micro, small and medium – sized enterprise (MSMEs) on economic growth in Deli Serdang for the period 2012 – 2021. This is a quantitative descriptive analysis utilizing secondary data from the Ministry of Cooperatives and Enterprises, Small and Medium Enterprises, and the Central Bureau of Statistics (BPS) Deli Serdang for time series data. Simple regression analysis, the t-test, and the coefficient of determination are utilized to test hypotheses (R2). Based on the findings of the t-test, it was determined that the influence of MSMEs on economic growth in Deli Serdang between 2012 and 2018 was considerable. The influence of MSMEs on economic growth in Deli Serdang was 80.2% as measured by the coefficient of determination (R2). Kata kunci: Micro, Small, and Medium – sized business; Economic Growth